New England 2025 - Harris, Patricia, 1949-; Lyon, David, 1949- (Eyewitness travel guides., 2025)
Whether you want to explore the rugged natural beauty of the Appalachian Mountains, follow the fascinating Freedom Trail through Boston, or indulge in fresh lobster from the coast of Cape Cod, your DK Eyewitness travel guide makes sure you experience all New England has to offer.